Influence of Y Zeolite Content on the Property of Zeolite Composite Materials - Sơn, Lê Thanh; Côn, Trần Hồng; Hương, Nguyễn Thị; Phương, Võ Hoàng (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: The materials based on organic silica and Y zeolite were synthesized from selt-assembly of polymethylhydrosiloxane, tetraethoxysilane and Y zeolite, using sodium hydroxide as catalyst. The structure characteristic and the porosity of the resultant mesoporous material were studied by SEM-EDX, XRD and the nitrogen adsorption isotherm techniques. Chemical bondings were characterized by using Fourier transform infrared spectroscope. Results indicate that the obtained materials exhibit the large surface area and porosity. Keywords: Y Z eolite, Zeolite composite, Polymethylhydrosiloxane, Tetraethoxysilane.